2022
DOI: 10.3389/fgene.2022.833190
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trajectories of Complex Traits in European Populations of Modern Humans

Abstract: Humans have a great diversity in phenotypes, influenced by genetic, environmental, nutritional, cultural, and social factors. Understanding the historical trends of physiological traits can shed light on human physiology, as well as elucidate the factors that influence human diseases. Here we built genome-wide polygenic scores for heritable traits, including height, body mass index, lipoprotein concentrations, cardiovascular disease, and intelligence, using summary statistics of genome-wide association studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…However, the study had limitations due to its small sample size (N = 99). Kuijpers et al (2022), with a larger sample of ancient genomes, confirmed these findings and observed an evolutionary acceleration post-Neolithic. Notably, their research depended on what was then an older PGS for education from Okbay et al (2016).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, the study had limitations due to its small sample size (N = 99). Kuijpers et al (2022), with a larger sample of ancient genomes, confirmed these findings and observed an evolutionary acceleration post-Neolithic. Notably, their research depended on what was then an older PGS for education from Okbay et al (2016).…”
supporting
confidence: 69%
“…Our analysis includes adjustments for ancestral background and geographic location. This study expands upon Kuijpers et al (2022) by using a GWAS based on a much larger sample (3 million individuals compared to 293,000) and focusing on different genetic traits. Unlike Kuijpers et al, we exclude medical phenotypes like lipoprotein levels and cardiovascular disease, instead incorporating mental health traits such as neuroticism, autism and schizophrenia.…”
mentioning
confidence: 99%
“…Previous studies have begun to explore the evolution of various complex traits by using ancient DNA [ 22 43 ]. In contrast to our investigation, these studies were based on pseudo-haploid genomes in which only one of the two alleles at each locus was randomly selected for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the true allele frequency is obscured, and the absence of a mutation can be artificially created. Recently, Kuijpers and colleagues used this method to show that HDL levels, an antagonist of atherogenesis, decreased consistently in European populations after the Neolithic Revolution [ 22 ]. However, in contrast to our study, they were not able to compare their genetic results with real phenotypes and the PRSs were calculated only for a haploid state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation